Neoliberal Globalisation and Islamic Social Movements: Critical Reflections on Approaches and Models - Amin, Husnul (Islamic Studies, 2012)
In the post September 11 era, considerable academic and semi-academic literature produced around the globe has addressed the diverse nature of responses to globalisation by the Islamic social trajectories in the Muslim world. Depending on opportunities and ideational frameworks of the Islamic movements, the variety of these responses range from complete rejection to partial acceptance to internalization. Looking at the empirical evidence of such an accommodating attitude of the Islamic social forces around the globe, the Islamophobic provocations may be questioned that see an essential antagonism between globalisation which is backed by the West and Islamic movements which are driven by religious ideologies. Predictions were also made about an inevitable clash between the two culturally incompatible entities, i.e., the West and Islam. A scenario of Jihad versus MacWorld and Mecca versus Mechanization was painted in the popular media. However, the recent scholarship has largely deviated from the trend and questioned not only the unstated assumptions of such approaches but also highlighted countless empirical examples that question the validity of an “us” versus “them” polarization. Using a snapshot approach, and keeping in background the accommodating attitude and amenability of Islamic social movements around the globe, this paper critically reviews some of the main theoretical threads deployed to the study of Islamic social movements. The paper addresses the ways these Islamic social forces have internalized these opportunities created by neoliberal globalisation specifically in the last three decades.